2008
DOI: 10.1016/j.ejcts.2008.03.060
|View full text |Cite
|
Sign up to set email alerts
|

Complete mediastinal lymphadenectomy: the core component of the multidisciplinary therapy in resectable non-small cell lung cancer

Abstract: There is a great deal of concern about metastasis of lung cancer to regional lymph nodes, due partly to the work of groups of thoracic surgeons in Japan and North America beginning in the 1970s. The classification of regional lymph node stations for lung cancer staging published by Mountain and Dresler has been widely adopted for more than ten years. Anatomic landmarks for 14 levels of intrapulmonary, hilar, and mediastinal lymph nodes stations are designated. Skip transfer and occult lymph node metastasis, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 63 publications
0
38
0
2
Order By: Relevance
“…As this trial greatly influenced surgeon assessment of mediastinal lymph 11 to 15 nodes conferred the lowest hazard ratio for death. Other authors recommend examination of a minimum of 10 lymph nodes and at least 3 lymph node stations [23,24]. The RNs greater than 10 in our patient cohort was predictive of nodal upstaging, but was not predictive of survival.…”
Section: Commentmentioning
confidence: 56%
“…As this trial greatly influenced surgeon assessment of mediastinal lymph 11 to 15 nodes conferred the lowest hazard ratio for death. Other authors recommend examination of a minimum of 10 lymph nodes and at least 3 lymph node stations [23,24]. The RNs greater than 10 in our patient cohort was predictive of nodal upstaging, but was not predictive of survival.…”
Section: Commentmentioning
confidence: 56%
“…However, others recommend examination of a minimum of 10 lymph nodes and at least three lymph node stations. 8,9 These harvested from at least three stations in 521 patients (99.4%). Combining these data, 516 (98.5%) had at least six lymph nodes examined from three lymph node stations and 469 (89.5%) had at least 10 lymph nodes examined from three stations.…”
Section: Discussionmentioning
confidence: 99%
“…16 nodes did not confer any further improvement in survival. 8,9 In a population-based study of 16,800 patients, multivariate analysis showed maximum survival for allcause mortality (hazard ratio, 0.78; 95% CI, 0.68-0.90) and lung-cancer-specific mortality (hazard ratio, 0.74; 95% CI, 0.62-0.89) in patients who had resection of 13 to 16 lymph nodes. 15 Similar results were reported by Ou and Zell 16 and Varlotto et al 17 Mature results of the ACOSOG Z0030 trial will provide level 1 evidence addressing the question of survival benefi t. 1 IIIA T2 N2 Squamous LUL 5 2 IIIA T2 N2 Adenocarcinoma LLL 9 3 IIIA T2 N2 Adenocarcinoma LUL 5, 11L 4 IIIA T2 N2 Squamous LUL 7 5 IIIA T2 N2 Bronchoalveolar LLL 7, 12L 6 IIIA T2 N2 Other NSCLC a LUL, LLL 11L b 7 IIIA T1 N2 Adenocarcinoma LUL 6, 12L 8 IIIA T1 N2 Adenocarcinoma LLL 6, 7, 11L 9 IIIA T1 N2 Other NSCLC a LUL 5, 12L 10 IIIA T2 N2 Adenocarcinoma RLL 7, 11R 11 IIIB T4 N2 Adenocarcinoma RUL 2R, 4R 12 IIIA T3 N2 Adenocarcinoma RLL 4R 13 IIIA T2 …”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Die systematische Lymphknotendissektion führt zu einem besseren Gesamtüberleben bei verlängertem krankheitsfreiem Intervall. Dabei ist die Morbidität und Mortalität bei der systematischen Lymphknotendissektion im Vergleich zum Lymphknoten-Sampling nicht erhöht [19]. Nur durch eine systematische Lymphknotendissektion ist es möglich, eine wirkliche komplette Resektion (R0) zu erreichen.…”
Section: Resektionsausmaß Bei Lymphogener Metastasierungunclassified